Agonists of peroxisome-proliferator activated receptor-gamma reduce renal ischemia/reperfusion injury - Sivarajah, A (2015)
Background/Aims: Recent evidence indicates that peroxisome-proliferator activated receptor (PPAR) agonists protect against ischemia/reperfusion (I/R) injury. Here we investigate the effects of the PPAR-gamma agonists, rosiglitazone and ciglitazone, on the renal dysfunction and injury caused by I/R of the rat kidney in vivo. Methods: Rosiglitazone or ciglitazone were administered to male Wistar rats prior to and during reperfusion. Biochemical indicators of renal dysfunction and injury were measured and histological scoring of kidney sections was used to assess renal injury. Expression of PPAR isoforms and intercellular adhesion molecule-1 during renal I/R were assessed using RT-PCR and Northern blot, respectively. Myeloperoxidase activity and activation of poly(ADPribose) polymerase (PARP) were used as indicators of polymorphonuclear (PMN) cell infiltration and oxidative stress, respectively. Results: Expression of PPAR-alpha, PPAR-beta and PPAR-gamma1 (but not PPAR-gamma2) was observed in kidneys with down-regulation of PPAR-a expression during renal I/R. Rosiglitazone and ciglitazone significantly reduced biochemical and histological signs of renal dysfunction and injury. Renal expression of ICAM-1 caused by I/R was reduced by rosiglitazone and ciglitazone which was reflected by decreased PMN infiltration into reperfused renal tissues. Both rosiglitazone and ciglitazone reduced PARP activation indicating a reduction of oxidative stress. Conclusion: These results suggest that the PPAR-gamma agonists rosiglitazone and ciglitazone reduce the renal dysfunction and injury associated with I/R of the kidney. We propose that one mechanism underlying the protective effects involves inhibition of the expression of ICAM-1, a reduction of PMN infiltration into renal tissues and subsequent reduction of oxidative stress. Copyright (C) 2003 S. Karger AG, Basel.